Extent of Disaster Management Program Implementation and Prepared-ness Level in Selected Public Secondary Schools in Zambales, Philippines - Viado, Alexander C.; Department, Jo A. Espiritu (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The research aimed to assess the implementation of various components of disaster management programs including Vulnerability Assessment, Planning and Preparedness, Institutional Framework and Coordination, Resource Management and Allocation, Early Warning Systems, Response Mechanisms and Emergency Operations, Public Education and Training Disaster Drills and Exercises. Additionally, the study aimed to determine the level of disaster preparedness among school personnel and students, identify any significant differences in program implementation among schools, and explore the relationship between program implementation and disaster preparedness. The data collection involved surveys, questionnaires, and interviews with school principals, teachers, and learners during the third quarter of the 2016-2017 school year. The sample consisted of six schools, and the gathered data were analyzed using appropriate statistical tools.The findings indicated that most of the disaster management activities were implemented in the schools within Zone IV, contributing to an effective implementation of the programs. Teachers were moderately prepared in planning and warning system activities but showed preparedness in other areas such as vulnerability assessment, planning and preparedness, institutional framework and coordination, resource management and allocation, early warning systems, response mechanisms and emergency operations, public education and training disaster drills and exercises. Similarly, students displayed moderate preparedness in warning system activities and preparedness in other aspects. Overall, the students in Zone IV were considered prepared for potential disasters in their community and school.